Mental and physical outcomes of yoga participation in women with spinal disorders: a qualitative study - Akyol, Gamze; Ağralı Ermiş, Sermin; Karakullukçu, Ömür Fatih; Güler, Özkan; Karakulak, İzzet; Arslanoğlu, Cansel; Satıcı, Arif; Sekban, Gülşah; Doğan, Erol; Şahin, Fatma Neşe; Küçük, Hamza (Frontiers in Public Health, 2025)
Yoga, a holistic practice supporting both physical and mental integrity, has gained increasing attention in recent years as a public health–promoting activity. Particularly among women with spinal disorders (e.g., hernia, lordosis, scoliosis, kyphosis), yoga is recognized not only for improving physical functionality but also for contributing significantly to psychosocial parameters such as stress management, self-awareness, and life satisfaction. In this context, the present study aimed to explore the mental and physical outcomes of regular yoga practice in women diagnosed with spinal disorders, using qualitative methods. This study was conducted using a phenomenological design, as the participants had experienced the situation under investigation. It included semi-structured, in-depth interviews with 15 adult participants diagnosed with spinal disorders and with at least 3 months of yoga experience. In line with the nature of qualitative research, the number of participants was deemed sufficient, and it was accepted that data saturation was reached through the interviews conducted with 15 participants. The findings revealed multidimensional benefits, including mental and physical relaxation, improved stress management, postural enhancement, better quality of life, and increased self-compassion. Participants also highlighted the positive influence of yoga on body–mind balance, awareness of personal limits, and a deeper understanding of their condition. These results suggest that yoga functions both as a physical intervention and a psychological support mechanism for women with spinal disorders, promoting active engagement in their treatment process and enhancing public health outcomes. In conclusion, yoga practice was found to provide significant and sustainable contributions to spinal health and overall psychosocial well-being.